Yield trends and changes in soil fertility in a long term pearl millet (Pennisetum glaucum)-wheat (Triticum aestivum) cropping system managed with organic, inorganic and integrated sources of nutrients - SHEORAN, SUNITA; ANTIL, R S; DEVRAJ, DEVRAJ; DEEPIKA, DEEPIKA; GREWAL, K S (The Indian Journal of Agricultural Sciences, 2018)
The present study was carried out to evaluate the yield trends and soil fertility under long term field experiment at soil research farm of CCS Haryana Agricultural University, Hisar, India. Results showed that average grain yield of wheat (Triticum aestivum L.) and pearl millet (Pennisetum glaucum (L.) R. Br) across the experimentation period was higher under integrated application of organic manures along with 150 kg N+30 kg P2O5/ha through chemical fertilizers as compared to application of recommended dose of nutrients through chemical fertilizers alone (150 kg N+60 kg P2O5/ha). Lowest grain yield of both crops was observed when organic manures applied alone. Positive yield trend of both the crops was observed under all the nutrient management practices. The highest soil organic carbon (SOC) (1.14%) was recorded with the application of farmyard manure (FYM) followed by pressmud and poultry manure. Build-up of organic carbon ranged from 0.016 to 0.037%/year with application of FYM, poultry manure, pressmud as a component of integrated nutrient management. Highest amount of humic acid-C (HA-C) and fulvicacid-C (FA-C) (0.40 and 0.21%, respectively) was observed with application of 7.5 Mg pressmud along with 150 kg N+30 kg P2O5 /ha. Integrated nutrient management (INM) showed superiority on better grain yield of pearl millet and wheat in these alluvial soils of Haryana.